The genesis of the development of the category of trust and mistrust in science - K. Ya. Litvina (Вестник Майкопского государственного технологического университета, 2024)
The Relevance. The initial manifestations of trust were recorded in the political philosophy of Ancient Greece and Ancient China, on the basis of which thinkers determined the interconnection and interdependence of relations between government and society. Further developing in line with political sociology, trust as the principle of “fides” (“faith”) from the Roman law was conceptualized by M. Weber as an “emotional product” of a social contract, violation of the terms of which does not carry sanctions, with the exception of the loss of business reputation. The category of trust was significantly enriched during the development of sociology of the 20th – early 21st centuries, and thanks to the works of P. Sztompka and F. Fukuyama, it gained understanding of the conditions for sustainable development of society in conditions of uncertainty, in which the individual proceeds from the “credit” of confidence in the respectable behavior of another and absolute confidence in one's own actions. In recent years, a “crisis of confidence” in science as a social institution in modern society has been recorded.The problem of the research is to identify the peculiarities of understanding the category of “trust” by the classics of sociological science and their applicability in modern science.The goal of the research is to study the relationship between the dynamics of trust in Sociology in the scientific community and in science as a social institution as a whole.The methodological basis of the reseearch is a systematic approach and general methods of scientific knowledge, such as analysis, synthesis, generalization.The Research results. The classics of sociological science have enriched the motivational, value and political meanings of the concept of «trust» in modern science.